Protection of the Customary Land of the Baduy Indigenous Peoples as One of the Supporting Factors for Local Food Security in the Banten Region - Jarkasi Anwar; Muhamad Muslih (Faculty of Law, Universitas Pekalongan, 2023)
The Baduy indigenous people as one of the ethnic groups in Indonesia have various unique and diverse cultural characteristics. The ethnic groups in Banten for hundreds of years have had their main livelihood, namely farming (ngahuma) and gardening to maintain survival in obtaining food so that this ngahuma is a form of food security for the Baduy indigenous people. Some of the Baduy's ulayat land is used for ngahuma and gardening. Recently, there has been an abuse of Baduy ulayat land by some irresponsible people. Mursyid's father as a traditional leader of the Inner Baduy does not agree with the existence of illegal gold mining around the Baduy area. This will disturb the land and forest ecosystems, especially since these customary rights are in the upstream area which will certainly cause negative things for the Baduy people. The gold mining will cause negative things for the environmental ecosystem in the Baduy area and even threaten the forests protected by the government. Baduy rejects the existence of gold mining if foreign companies exploit it. The expression of one of the Baduy community leaders,